Fiber sensor identification based on incoherent Rayleigh backscatter measurements in the frequency domain - Köppel, Max; Engelbrecht, Rainer; Werzinger, Stefan; Schmauß, Bernhard (International Conference on Optical Fiber Sensors (OFS), 2017)
In this work, a fiber identification method based on incoherent optical frequency domain reflectometry (IOFDR) measurements is introduced. The proposed method uses the characteristic interference pattern of IOFDR Rayleigh backscatter measurements with a broadband light source to unambiguously recognize different initially scanned fiber segments. The recognition is achieved by cross-correlating the spatially resolved Rayleigh backscatter profile of the fiber segment under test with a initially measured and stored backscatter profile. This profile was found to be relatively insensitive to temperature changes. It is shown that identification is possible even if the fiber segment in question is installed subsequent to 300m of lead fiber. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Koeppel2017a